The Effect of Combination Foot Massage and Active Range of Motion (ROM) on Foot Sensitivity among Patients with Type 2 Diabetic Mellitus - I Made Cahyadi Agastiya; Ni Ketut Romani; I Made Artana (Babali Nursing Research)
Introduction: T2DM can increase morbidity and mortality. Almost half of T2DM patients have impaired foot sensitivity. This increases the risk of diabetic foot ulcers, causing the patient to not feel any injuries to the legs, even to amputation. Therefore, handling the proper treatment to prevent these complications is necessary, one of which is using foot massage and active ROM. This study aimed to determine the effect of the combination of foot massage and active ROM on foot sensitivity among T2DM patients at Mangusada Hospital.